The Risk of Upper Urinary Tract Involvement in Patients With Ketamine-Associated Uropathy - Chi-Hang Yee; Jeremy Yuen-Chun Teoh; Pui-Tak Lai; Vivian Yee-Fong Leung; Winnie Chiu-Wing Chu; Wai-man Lee; Yuk-Him Tam; Chi-Fai Ng (International Neurourology Journal, 2017)
Purpose The aims of this study were to investigate the prevalence of upper tract involvement in ketamine-associated uropathy, and to determine the predictors of hydronephrosis in patients with a history of ketamine abuse. Methods This was a cross-sectional study of a prospective cohort of patients with ketamine-associated uropathy. Data including demographics, pattern of ketamine abuse, pelvic pain and urgency or frequency (PUF) symptom score, uroflowmetry (UFM) parameters, serum renal function, and liver function tests were collected. Upon consultation, ultrasonography was performed to assess the function of the urinary system. Results From December 2011 to October 2015, we treated 572 patients with ketamine-associated uropathy. Of these patients, 207 (36.2%) had managed to achieve abstinence at the time of their first consultation. Ninety-six patients (16.8%) in the cohort were found to have hydronephrosis on ultrasonography. Univariate analysis identified age, duration of ketamine abuse, PUF symptom score, voided volume on UFM, serum creatinine levels >100 μmol/L, and an abnormal serum liver enzyme profile as factors associated with hydronephrosis. Logistic regression revealed the following parameters to be statistically related to hydronephrosis: age (adjusted odds ratio [OR], 1.090; 95% confidence interval [CI], 1.020–1.166; P=0.012), functional bladder capacity (adjusted OR, 0.997; 95% CI, 0.995–0.999; P=0.029), serum creatinine >100 μmol/L (adjusted OR, 3.107; 95% CI, 1.238–7.794; P=0.016, and an abnormal serum liver enzyme profile (adjusted OR, 1.967; 95% CI, 1.213–3.187; P=0.006). Conclusions Ketamine-associated uropathy can involve the upper urinary tract. Patient demographics as well as investigations of UFM, renal function tests, and liver function tests may allow us to identify at-risk patients.